Education and gender-based differences in employee motivation - Hitka, Miloš; Kozubíková, Ľudmila; Potkány, Marek (Journal of Business Economics and Management, 2018)
The main purpose of this article is to show dependencies between education and gender based on selected motivation factors. In order to obtain relevant data, the questionnaire method was used. In the years 2013–2016, 26,416 respondents participated. Descriptive statistics was used for data processing; the relationship between two categorical variables was verified by the chi-quadrate test and Tukey’s HSD test. The results of the research proved the hypotheses; i.e. that there are significant differences in motivation factors among Slovak employees related to their gender and education. The most significant motivation factors included basic salary, job security and a good working team. The paper presents an original verifiable methodology that can be used in research of a similar focus in other European countries. The research results point to the potential of various alternatives for business managers responsible for preparing incentive motivation programmes related to the analysed factors.